Motor activity and neurological deficit restoration as the result of combined semax and hopantenic acid influence in experimental chronic brain ischemia - Kirchev, V. (Journal of Education, Health and Sport, 2024)
The prevalence and incidence of cerebrovascular pathology, especially chronic progressive forms, is constantly increasing in modern conditions. Treatment of chronic forms of cerebral blood supply insufficiency is of particular relevance. The insufficient of postischemic disorders efficacy correction and/or behavioral manifestations is justified by the insufficient study of the pathogenetic mechanisms of this complex cerebrovascular catastrophe, which results in insufficiently effective efforts to implement sanogenetic effects. The purpose of the work was the determine the efficacy of Semax and hopantenic acid administration in the treatment of motor disorders and neurological disorders in rats with experimental chronic brain ischemia. Within 7 days, in rats with a model of chronic brain ischemia by bilateral ligation of the carotid arteries, motor activity in the “open field” test and neurological deficit were determined after separate and combined administration of Semax and hopantenic acid. The formation of motor behavior changes and expressed neurological deficit in the dynamics of the post-ischemic period was proved. Semax and hopantenic acid separate and combined administration contributed to horizontal and vertical locomotor behavior normalization of animals in the “open field” test as well as neurological deficit almost complete elimination. The author believe that the obtained data are an experimental basis for the feasibility of clinical testing of the nootropic effects of Semax and hopantenic acid combined administration in chronic brain ischemia.